Firm Characteristics and Earnings Management: Does Governance Still Matter? - Rafrini Amyulianthy; Harnovinsah Harnovinsah; Adriana Putri (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study examines how firm size and leverage influence earnings management and whether corporate governance mechanisms moderate these relationships, grounded in legitimacy theory.Research Methodology: Moderated Regression Analysis (MRA) was applied to 135 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2023.Results: Larger and more leveraged firms tend to engage in earnings management to preserve legitimacy. Audit committee meeting frequency significantly reduces earnings management and weakens the positive effects of both firm size and leverage on it. Board of commissioners meeting frequency also negatively affects earnings management and attenuates the leverage–earnings management relationship; however, it paradoxically amplifies the firm size–earnings management relationship, suggesting that governance formality without substantive oversight may be counterproductive.Conclusions: Active audit committees serve as effective deterrents to earnings management, while the board of commissioners produces mixed moderating effects depending on the quality of engagement. Regulators and firms should prioritize substantive governance practices over mere formal compliance.Limitations: Findings are confined to IDX-listed manufacturing firms in 2023, with earnings management proxied through Jones discretionary accruals and governance measured solely by meeting frequency. Caution is advised when generalizing across sectors or different macroeconomic conditions.Contributions: This study enriches legitimacy theory by explaining earnings management behavior in Indonesian manufacturing firms. Empirically, it highlights audit committee effectiveness as a critical deterrent to earnings management, offering practical guidance for regulators and companies to prioritize substantive governance over formal compliance.